PEMODELAN PERPINDAHAN PANAS PROSES PENDINGINAN TERAK SEMEN DALAM GRATE COOLER - Darmanto, Prihadi Setyo; Sugiharto, Sri (Mesin, 2004)
Cooling of clinker into grate cooler is one of important processes in cement manufacturing because it influences the quality of the clinker and also determines heat recovery of the combustion air which related well to the fuel consumption. Heat transfer mechanism of the clinker cooling comprises radiation, convection, and conduction. This paper presents a numerical method of clinker cooling process on a grate cooler in order to evaluate temperature distribution of both clinker and cooling air in vertical and horizontal directions along the grates. The result was validated with the measurement of clinker temperature at the discharge section of the cooler. The proposed evaluation method will pave the way for determining the constant values of the control system for cooling air..